2015
DOI: 10.5406/womgenfamcol.3.2.0144
|View full text |Cite
|
Sign up to set email alerts
|

Employment Outcomes among African American and White Women with Disabilities: Examining the Inequalities

Abstract: Compared to individuals without disabilities, those with disabilities experience inequalities in finding and sustaining employment that are more profound among women and minorities. The purpose of this study is to examine differences in employment outcomes for African American and white women with disabilities who received vocational rehabilitation (VR) services. The VR data that this study used included 18,602 women, 18-65 years old at entry into the VR system in a Midwestern state. Using logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…For example, although Black people generally have less access to updated technology for job applications and college courses, this issue is not consistently taken into account when job counselors are preparing vocational plans (Vryhof & Balcazar, 2020). In addition, many Black people with SMI don't know about the availability of and eligibility standards for formal vocational supports such as Vocational Rehabilitation, One-Stop Career Centers, and Independent Living Centers (Oberoi et al, 2015). Since they are less likely to seek mental health services than White people, they are more likely to miss out on vocational services embedded within such programs (Anderson, 2018).…”
Section: Black Young Adults With Serious Mental Illnessesmentioning
confidence: 99%
“…For example, although Black people generally have less access to updated technology for job applications and college courses, this issue is not consistently taken into account when job counselors are preparing vocational plans (Vryhof & Balcazar, 2020). In addition, many Black people with SMI don't know about the availability of and eligibility standards for formal vocational supports such as Vocational Rehabilitation, One-Stop Career Centers, and Independent Living Centers (Oberoi et al, 2015). Since they are less likely to seek mental health services than White people, they are more likely to miss out on vocational services embedded within such programs (Anderson, 2018).…”
Section: Black Young Adults With Serious Mental Illnessesmentioning
confidence: 99%
“…1,5 Black people with disabilities are less likely to be accepted for government funded vocational rehabilitation (VR) services than White peers. 6 If accepted into VR, minorities are less likely to receive training or have their cases closed successfully when compared to people who are White with disabilities. 6 A study using VR data found that the VR cases of Black clients with mental health conditions, if screened in, were more likely to be closed as non-rehabilitated when compared to White clients with mental health conditions.…”
Section: The Problemmentioning
confidence: 99%
“…Individuals with disabilities from racial and ethnic minority backgrounds often experience challenges when applying for social services like vocational rehabilitation (which provides supports for pursuing employment and educational opportunities), including difficulties in obtaining all required documents, difficulties meeting eligibility criteria, and receiving fewer services than some white consumers (Oberoi, Balcazar, Suarez‐Balcazar, Langi, & Lukyanova, ; Taylor‐Ritzler, Balcazar, Suarez‐Balcazar, & Garcia‐Iriarte, ). Moreover, these individuals are also underserved by health services and, as a result, they are likely to have limited access to preventive treatments and experience secondary conditions (Suarez‐Balcazar, Balcazar, Taylor‐Ritzler et al., ).…”
Section: Future Directions In Disability Research From a Community Psmentioning
confidence: 99%